HUBUNGAN TINGKAT KEPATUHAN TERAPI ANTIHIPERTENSI DENGAN RISIKO KARDIOVASKULAR DI PUSKESMAS CIKARANG - Anggita, Rahmi; Marselina; Adwisastra, Nuzul Gyanata; Dewi, Masita Sari (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Hypertension is a major risk factor for cardiovascular disease. However, evidence regarding the association between adherence to antihypertensive therapy and cardiovascular risk remains inconsistent, particularly in primary care settings. This study was conducted at Cikarang Community Health Center, where hypertension is among the top ten most prevalent diseases. The objective was to determine the relationship between adherence to antihypertensive therapy and cardiovascular risk. A cross-sectional analytical study was conducted on 85 purposively selected hypertensive patients. Adherence was assessed using MARS-5 and Medication Possession Ratio (MPR), while cardiovascular risk was calculated with the ASCVD score. Data were analyzed using Chi-Square, linearity test, and Odds Ratio. Results showed that most patients were adherent (MARS-5 = 91.8%; MPR = 76.5%) and had low cardiovascular risk (64.7%). There was a significant association between adherence and cardiovascular risk (MARS-5 p=0.041; MPR p=0.049). Adherent patients were more likely to have lower cardiovascular risk. In conclusion, higher adherence is associated with lower cardiovascular risk. Continuous education and routine monitoring are essential to maintain adherence and prevent complications.